Wayward lives and beautiful experiments: Sex, dance, jazz and gender in the world of the pre-WWII ‘chorus girl’ - Smith, Christopher J (Jazz Research Journal, 2022)
Saidiya Hartman’s 2021 Wayward Lives, Beautiful Experiments literally re-imagines the experience of young black women in 1910s New York, employing a method Hartman calls ‘critical fabulation’, in which—rather in the form of retconned speculative fiction—she teases out gaps in the archival record. Employing Hartman’s own call-and-response technique of rhetorical questions which spotlight the uncertain answers to questions about minoritized human experience, I ask: ‘How did the “light-skinned chorines” in multi-racial 1930s nightclub and theater culture create spaces of “beautiful experiment” within their day-to-day? How did the “noisy” dance of jazz reinscribe—or subtly subvert—the white racist gaze? What did the chorines think about all this?’ This creative non-fiction essay imagines responses.